Synthesis of trackless emulsified asphalt tack coat with gradient distribution of polyurethane via self-migration and its performance evaluation - Feng, Xuemao; Zhou, Gaowei; Wang, Hongwei; Lv, Libo; Qin, Zixuan; Ma, Qing; Li, Wenrui; Huang, Wei (Frontiers in Materials, 2025)
A new type of trackless emulsified asphalt (TEA) tack coat with a gradient distribution of polyurethane (PU) was prepared via self-migration technology to solve the problems of tracking and poor bonding in common tack coats. The PU distribution in the vertical section of tack coat was characterized by electron microscopy, Fourier transform infrared spectroscopy (FTIR), and contact angle tests. The basic performance of TEA, such as penetration, ductility, softening point, rheological properties, and storage stability, was studied. The pavement performance of TEA tack coat was evaluated by track-free time, tracking resistance, and shearing resistance tests. The results indicate that the gradient distribution of PU (PU content increasing from bottom to apparent) was formed in tack coat. Based on tests on tracking resistance, non-tracking time, and storage stability, an optimal dosage of 3% polyurethane latex modifier was determined. For TEA-3 (with 3% polyurethane latex modifier), the non-tracking time at 35°C was decreased to under 30 min. This substantial reduction significantly enhanced its construction efficiency. Mechanical performance evaluations of TEA-3 demonstrated exceptional temperature resistance, maintaining shear strength exceeding 1 MPa at 60°C while remaining track-free at 70°C. The uniform dispersion of PU within the TEA tack coat matrix contributed to substantial improvements in both track-free characteristics and interfacial shear resistance, even at minimal PU modification levels. The material combines excellent road performance and environmentally friendly preparation process, providing a promising technical solution for the application of tack coat in the field of road engineering.